2015
DOI: 10.1103/physreve.91.033010
|View full text |Cite
|
Sign up to set email alerts
|

Upscale energy transfer and flow topology in free-surface turbulence

Abstract: Free-surface turbulence, albeit constrained onto a two-dimensional space, exhibits features that barely resemble predictions of simplified two-dimensional modeling. We demonstrate that, in a three-dimensional open channel flow, surface turbulence is characterized by upscale energy transfer, which controls the long-term evolution of the larger scales. We are able to associate downscale and upscale energy transfer at the surface with the two-dimensional divergence of velocity. We finally demonstrate that surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
(32 reference statements)
0
10
2
Order By: Relevance
“…First, no evident −5/3 range is observed except for few of the lowest wave numbers: This can be attributed to the intermittent nature of turbulence associated with spatial fluctuations in the rate of energy dissipation. A relatively larger range of high wave numbers can be identified over which spectra exhibit a −3 scaling: In the present flow configuration, however, this corresponds to up-cascading of energy from large to small wave numbers, namely, to merging of smaller flow structures into larger structures [29]. Such findings cannot be reconciled with the KLB theory for 2D turbulence.…”
Section: A Flow Field Characterizationcontrasting
confidence: 58%
See 2 more Smart Citations
“…First, no evident −5/3 range is observed except for few of the lowest wave numbers: This can be attributed to the intermittent nature of turbulence associated with spatial fluctuations in the rate of energy dissipation. A relatively larger range of high wave numbers can be identified over which spectra exhibit a −3 scaling: In the present flow configuration, however, this corresponds to up-cascading of energy from large to small wave numbers, namely, to merging of smaller flow structures into larger structures [29]. Such findings cannot be reconciled with the KLB theory for 2D turbulence.…”
Section: A Flow Field Characterizationcontrasting
confidence: 58%
“…The effect of imposing the flat surface does not alter the turbulence in the bulk of flow, as it is constantly generated from the bottom wall (source of shear). The choice of imposing a flat free surface has been discussed in Lovecchio et al [18] and is motivated by previous findings [24,[29][30][31], which have shown that light particles moving at the deformed free surface of a turbulent flow are subject to clustering mechanisms that come from the horizontal divergence at the surface: These mechanisms induce a compressible effect similar to the one observed over flat surfaces.…”
Section: Physical Problem and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…also [43]. Furthermore, recent investigations [42] show a three-dimensional character of the turbulent flow at free surfaces; however, implications with regard to boundary conditions for the bulk flow seem to be uncertain at present. For the present analysis, it may be seen as reassuring that the application of the conventional boundary conditions (16a) and (16b) in previous work has led to reasonable agreement with measurements of surface elevation as well as shear stress distribution for both undular jumps [25,35,36,61] and stationary solitary waves [62].…”
Section: (Xh )mentioning
confidence: 99%
“…m , according to (37) and (42), respectively. a Plane ramp with height ψ ∞ and length L. First-order eigenvalue ψ ∞ = 12. b Bump with isosceles triangular cross section of height ψ(0) and half-length L…”
Section: Solution Of the First Kind (Solitary-wave Type) For A Plane mentioning
confidence: 99%